Efeitos da ovariectomia, estrógeno e isoflavonas da soja em glândulas sumandibulares de ratos - Vasconcellos, Luana Marotta Reis [UNESP]; Silveira, Vanessa Avila Sarmento [UNESP]; Medeiros, Raphaella Silveira [UNESP]; Amorim, Márian Yaktin [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Prado, Renata Falchete [UNESP] (Editora Cubo, 2017)
Objective: A decrease in granular convoluted tubule (GCT) cells and acini occurs in the submandibular glands of castrated female rats, while in rats submitted to hormone replacement and phytotherapy with soy isoflavones, this effect is reversed. This study aimed to elucidate the mechanisms through which these changes occur. Material and Methods: Rats (n=84) were ovariectomized and 21 were sham-operated. Ovariectomized rats were randomly subdivided and orally administered the following: 17 β-estradiol (OVX-E; n=21), 15 mg/kg/day of soy isoflavone extract (OVX-I; n=21), 17 β-estradiol + soy isoflavone extract (OVX-A; n=21); and water as placebo (OVX; n=21). The rats were euthanized three, five and eight weeks after ovariectomy. The submandibular salivary glands were submitted to histological processing with HE stain and immunohistochemistry was performed using the streptavidin-biotinperoxidase complex. The cell area and the expression of proliferating cell nuclear antigen and estrogen receptor β were evaluated. Results: The results were statistically analyzed by ANOVA and Tukey test. A decrease in the area of GCT cells in the OVX, was observed, in contrast with an increase in the OVX-E. PCNA in the acinar cells and estrogen receptors were elevated in the OVX-I group. Conclusion: Castration exerts an immediate reductive effect on the volume of GCT cells. Estrogens, soy isoflavones and their combination have different mechanisms of action on the homeostasis of the gland. Estrogens cause an increase in GCT cells area, while isoflavones enhance cell proliferation and the expression of estrogen receptor-β. Their association showed no additional increase in the effect studied.
Effects of ovariectomy, estrogen and soy isoflavones in rats submandibular glands
Keywords: Estrogen; Morphometry; Salivary glands; Soy isoflavones